2020
DOI: 10.1177/2053434520907743
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative research on co-creating care pathways for Sarcoma and GIST by stimulating reflection

Abstract: Introduction Care Pathway Management intends to enhance the quality of care by restructuring care services. As recipients of care, patients have relevant experiential knowledge on the provision of care, but they are rarely involved in Care Pathway Management due to various barriers. This study aims to acquire insights into how patients can be meaningfully involved in Care Pathway Management. Methods A case study was conducted to assess the implementation of patient involvement in the co-creation of the care pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Clinicians also expressed that their skillsets and, for some, multiple skillsets, played an important role in the meaningfulness and depth of their contribution. Petit-Steeghs et al (2020) conducted a thematic analysis of interviews with patients and providers participating in the co-creation of a clinical care pathway for sarcoma and gastrointestinal stromal tumours [ 40 ]. They identified a power-imbalance between the patients and providers.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians also expressed that their skillsets and, for some, multiple skillsets, played an important role in the meaningfulness and depth of their contribution. Petit-Steeghs et al (2020) conducted a thematic analysis of interviews with patients and providers participating in the co-creation of a clinical care pathway for sarcoma and gastrointestinal stromal tumours [ 40 ]. They identified a power-imbalance between the patients and providers.…”
Section: Discussionmentioning
confidence: 99%
“…A gap tool was developed that could be used to provide structured interrogation of the information available for each of the final 70 initiatives. The gap tool was co-created and tested in an iterative manner through two multi-stakeholder workshops and two online webinars with consortium partners, based on foundational conditions and principles for successful collaborations with public and/or patients in decision-making processes [5,6,30,31]. The principles and conditions were used to help map findings from a recent monitoring and evaluation review [2] and output and outcomes criteria from a multi-stakeholder Delphi method into forty-six criteria organised under fourteen themes (Table 2).…”
Section: Stage 2: Gap Tool Development For Evaluation Of Initiativesmentioning
confidence: 99%
“…It was found that the co-creation process encountered several barriers, including limited opportunities to overcome patients' knowledge gaps on medical services, limited time, and uncertainties about responsibilities. 6 By evaluating the effectiveness of stakeholder engagement on a digital platform in the Netherlands, Toninic et al show how such a platform for the co-creation of health care innovations can be further improved to support potentially high-impact care innovations from an early phase. 7 Finally, an example of taking a broader lens when looking at the coordination of services is offered by Towe et al 8 In evaluating pre-data integration for health information technologies to share patient and housing data for improving the treatment of patients with HIV in the United States of America, they identified several essential activities that require consideration, including the identification of partners, data integration model, and functionality selection.…”
mentioning
confidence: 99%